Tesco in South Korea : strategic localization - Robson, Karen, (Assistant professor), (SAGE Knowledge. Cases., 2018)
The U.K.'s largest supermarket chain, Tesco, entered the South Korean market in 1999 through a joint venture with the Korean firm Samsung. Operating under the name Homeplus, the company steadily increased their market share over the years, and eventually launched "virtual stores" that were tailored specifically to the needs of local shoppers. Consumers on their way to work could visit a "virtual store" along their commute, purchase items through an app on their phone, and then schedule delivery for a convenient time that same day. By 2011, Tesco's business in South Korea had grown to its largest outside of the U.K., with revenues of almost ?5 billion. However, in 2012, regulations changed again, leaving the company unable to operate on some of its busiest days. This case explores Tesco's strategy of strategic localization in South Korea and asks students to consider how the company should respond to the new regulations. Could Tesco continue to be successful by operating in South Korea?